2017
DOI: 10.1016/j.frl.2016.12.034
|View full text |Cite
|
Sign up to set email alerts
|

An examination of investors’ reaction to the announcement of CoCo bonds issuance: A global outlook

Abstract: Major international financial institutions (FIs) are using contingent convertible (CoCo) bonds in the wake of the 2008 financial crisis to meet stricter national and international capital requirements. Beginning with UniCredit's €500m 9.375% CoCo in July 2010, more than 40 publically held financial institutions headquartered in 16 countries have issued 68 CoCos. This paper examines investors' reactions to the announcements of CoCo bonds issuances by FIs. Using event-study methodology and measuring cumulative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
(8 reference statements)
1
15
0
4
Order By: Relevance
“…The determinations of the Basil Accords and their effects have been the object of considerable attention on the part of researchers and players in the market, because of the importance of their guidelines in ensuring the solidity and stability of the financial markets, as well as their wide scope -since they have been adopted by numerous countries in different continents. This is particularly the case in regards to the effects of issuing instruments to meet the requirements of capital, the object of this study, and have been found in some other studies in the international sphere, among which attention should be drawn to those of Schmidt and Azarmi (2015), Avdjiev et al (2015), Ammann et al (2017) and Liao et al (2017). As all these studies were based on instruments with a convertibility clause, the IDECs that are designated CoCos.…”
Section: Studies On the Reaction Of The Market To The Issuance Of Idecmentioning
confidence: 73%
See 4 more Smart Citations
“…The determinations of the Basil Accords and their effects have been the object of considerable attention on the part of researchers and players in the market, because of the importance of their guidelines in ensuring the solidity and stability of the financial markets, as well as their wide scope -since they have been adopted by numerous countries in different continents. This is particularly the case in regards to the effects of issuing instruments to meet the requirements of capital, the object of this study, and have been found in some other studies in the international sphere, among which attention should be drawn to those of Schmidt and Azarmi (2015), Avdjiev et al (2015), Ammann et al (2017) and Liao et al (2017). As all these studies were based on instruments with a convertibility clause, the IDECs that are designated CoCos.…”
Section: Studies On the Reaction Of The Market To The Issuance Of Idecmentioning
confidence: 73%
“…Another similar study was carried out by Liao et al (2017), which employed a study of key events to analyze the effects of 68 announcements of the issuance of CoCos, for 46 banks in 16 countries -China, Australia, India, Malaysia and 12 European countries -in the period 2010 -2014. After estimating the Cumulative abnormal return -CAR) in the period of 15 days before and 15 days after the announcements of the issuance of CoCos, the authors found out that the banks usually experience negative abnormal returns in the immediate aftermath of the announcement.…”
Section: Studies On the Reaction Of The Market To The Issuance Of Idecmentioning
confidence: 99%
See 3 more Smart Citations